1988
DOI: 10.1128/jcm.26.4.726-731.1988
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three techniques for detection of Chlamydia trachomatis in endocervical specimens from asymptomatic women

Abstract: Culture in DEAE-dextran-treated HeLa 229 cells, a solid-phase enzyme immunoassay (EIA) (Chlamydiazyme; Abbott Laboratories, North Chicago, 111.), and a direct immunofluorescence test (DFA) (MicroTrak; Syva Co., Palo Alto, Calif.) were compared for the detection of Chlamydia trachomatis in endocervical specimens from 715 asymptomatic women. Response to antibiotic therapy was also monitored at least 4 weeks after completion of therapy. An additional sample was collected at a control visit, and a second culture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 29 publications
5
22
0
1
Order By: Relevance
“…These findings reflect the low prevalence of sexually transmitted disease present in the women attending gynecological clinics at our hospital. The results of this study are also consistent with the experience of other investigators (8,11) who have evaluated nonculture methods for the diagnosis of C. trachomatis in similar populations with a low prevalence of infection.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These findings reflect the low prevalence of sexually transmitted disease present in the women attending gynecological clinics at our hospital. The results of this study are also consistent with the experience of other investigators (8,11) who have evaluated nonculture methods for the diagnosis of C. trachomatis in similar populations with a low prevalence of infection.…”
supporting
confidence: 91%
“…The introduction of commercial kits with species-specific monoclonal antibodies that detect chlamydial antigens in the outer membrane protein and genus-specific antibodies to cell wall lipopolysaccharide has permitted the development of techniques for more rapid testing of specimens. Both enzymelinked immunoassay and direct fluorescent-antibody (DFA) methods are available (7,8,11,14,15). Several new rapid tests that are easier to perform and that do not require the purchase of expensive supplementary equipment have also been introduced (4).…”
mentioning
confidence: 99%
“…The DFA test for C. iruchornutis appears to be equally effective in both symptomatic and high-risk, high prevalence ( > 10"h) asymptomatic female subjects (8,11). However it is not recommended for low-risk populations as a screening test (2,3,6). In our research we found the prevalence rate in the asymptomatic group to be 23%.…”
Section: Discussionmentioning
confidence: 54%
“…The specimens that were found positive were retested and reconfirmed by the direct immunofluorescent test (Biomerix). The sensitivity for this test is 81.1% and specificity is 97.9% (6). This protocol was used to eliminate the false positive tests in the study.…”
Section: Fp = Family Planning Clinicmentioning
confidence: 99%